Guide to MARC 21 : for cataloging of books and serials - Mukhopadhyay, Asoknath (New Delhi : Viva books private limited, 2007)
Guide to MARC 21 serves as a comprehensive handbook to MARC catalogers and as learning resource to students. Practising MARC catalogers must apply the right MARC 21 content designators while inputting bibliographic information for effective resource-sharing and networking. But going through the massive learning resources on MARC completely unguided is almost like crossing a desert all alone." "The book explains with examples the scope, content designations and interpretations of the MARC fields for cataloging language materials - mainly books and serials. The terminology and definitions used are in tune with MARC documentation, CCP, OOCL, AACR2 and ISBD. Based on the most recent updates to MARC, it offers field- and subfield-specific interpretations of rules and provides plenty of examples for the appropriate use of tags, delimiters and data renderings. It also contains a bibliography, a webography and a list of gateways that give authentic information sources about MARC-compatible library software, utilities, freely accessible databases of MARC records and online cataloging norms and practices.
one CD
Keywords: MARC formats; Machine-readable bibliographic data; Electronic documents